Diagnostic assays developed for the control of foot-and-mouth disease in India - Sharma, Gaurav Kumar (World J Virol, 2015)
Foot-and-mouth disease (FMD) is a highly contagious and economically devastating disease of livestock, primarily affecting cattle, buffalo and pigs. FMD virus serotypes O, A and Asia1 are prevalent in India and systematic efforts are on to control and eventually eradicate the disease from the country. FMD epidemiology is complex due to factors like co-circulation, extinction, emergence and re-emergence of genotypes/lineages within the three serotypes, animal movement, diverse farm practices and large number of susceptible livestock in the country. Systematic vaccination, prompt diagnosis, strict biosecurity measures, and regular monitoring of vaccinal immunity and surveillance of virus circulation are indispensible features for the effective implementation of the control measures. Availability of suitable companion diagnostic tests is very important in this endeavour. In this review, the diagnostic assays developed and validated in India and their contribution in FMD control programme is presented.